Effectiveness of varietal resistance and risk prediction for the control of ramularia leaf spot of barley under Irish growing conditions. (January 2021) - Mulhare, Joseph; Creissen, Henry E.; Kildea, Steven
Abstract: Ramularia leaf spot (RLS) of barley, caused by the fungal pathogen Ramularia collo-cygni, is a significant threat to the viability of spring barley production in Ireland. As a relatively new disease of barley, limited information is available on the development and impact of the disease under Irish conditions. RLS symptoms often only develop after anthesis and the final fungicide application, therefore some decision support is required for growers to be able to make sound integrated pest management (IPM) decisions. In the present study field trials were conducted on spring barley in 2016–2018 to determine if environmental conditions during stem extension, specifically leaf wetness, could be used to aid decisions relating to the intensity of fungicide control required later in the season for the control of RLS. The trials were conducted on four spring barley varieties subjected to one of five fungicide treatments at awn emergence 1) untreated control 2) pyraclostrobin 3) prothioconazole and chlorothalonil 4) decreased/increased rates of prothioconazole and chlrothalonil depending on risk of RLS development and 5) exclusion of prothioconazole or addition of bixafen depending on risk of RLS development. In 2018, although moderate-high levels of disease were predicted, a prolonged dry period post-stem extension resulted in no disease development. In 2016, 2017 moderate levels of disease developed in the trials, with various significant ( P  < 0.05) interactions recorded between site, year, variety and fungicide treatment, depending on specific variable assessed: visual leaf symptoms, pathogen load in the leaf or grain as determined by qPCR or final grain yield. This was further evident in the relationships between visual symptoms and detectable R. collo-cygni biomass in the leaf with yield, these contrasted between seasons with weak relationships detected in 2016 ( R 2  = −0.019 and R 2  = 0.176 for visual and biomass respectively) and strong relationships detected in 2017 ( R 2  = −0.748 and R 2  = −0.5 for visual and biomass respectively). The variability in responses to the variety and fungicide treatments and the relationships between visual disease symptoms and biomass further highlight the unpredictability of RLS. Highlights: High levels of ramularia leaf spot (RLS) can significantly impact spring barley yields in Irish growing conditions. Minutes of leaf wetness during stem extension did not always contribute to levels of RLS. Multiple interactions between year, site, cultivar and fungicide treatment were observed highlighting the complexity of RLS. Differences in cultivar resistance to RLS exist and further research is required to further exploit these differences.